VD_FINDINFO Plainte / 2015 / 36 vom 13. Oktober 2015 - VD Tribunal cantonal (2015)
PLAINTE PÉNALE, PLAINTELP, RÉVOCATIONEN GÉNÉRAL, CESSION DES DROITS DE LA MASSE, NULLITÉ, DROIT D'ÊTRE ENTENDU, RESTITUTION DU DÉLAI | 29 al. 2 Cst., 17 al. 1 LP, 17 al. 2 LP, 22 al. 1 LP, 260 LP, 33 al. 4 LP